Proving the value of HR : how and why to measure ROI - Phillips, Jack (Society For Human Resource Management, 2012)
In practice, ROI [return on investment] must be explored, considered, and ultimately implemented in almost every organization--whether it is for profit or nonprofit, public or private. What was needed, according to HR practitioners, was a book that addresses the ROI process for human resources and presents an approach that is rational, feasible, and understandable to the typical HR practitioner. Proving the Value of HR is designed to meet that need. This book presents the ROI model in a step-by-step process. A chapter is devoted to each major part of the model as the pieces of the ROI puzzle are methodically assembled. The new edition has also been significantly reorganized and includes new information, examples, and a few new techniques.